Mediasi Intellectual Capital atas Pengaruh Digital Marketing Terhadap Kinerja Pemasaran - Sidi, Agus Purnomo; Yogatama, Ahmad Nizar (Fakultas Ekonomi, UIN Maliki Malang, 2019)
Today's world has been facing a new era that emphasizes every creative industry to overcome information technology, especially for selling and marketing needs, namely the digital era. In this era of disruptive technology, company size cannot be guaranteed, so that the creative industries processing waste and used goods can take this opportunity to penetrate domestic and international markets. The success of innovative products penetrating the global market will provide enormous benefits for the industries that show one of marketing performance, especially if it is balanced by high intellectual capital. The purpose of this study is to determine the direct and indirect effects of digital marketing on the marketing performance of creative industries processing waste and used goods through intellectual capital. The population of this research is the entire creative industries entrepreneurs processing waste and used products in Malang town whose numbers are unknown. The research sample of 150 respondents was selected through accidental-purposive-sampling technique. Quantitative primary data were collected through questionnaire surveys and analysed using path analysis. The results showed that digital marketing has direct and indirect effects on marketing performance through intellectual capital as an intervening variable which these effects are positive and significant